Digital Technologies for Health Workforce Development in Low- and Middle-Income Countries: A Scoping Review - Long, Lesley-Anne (Glob Health Sci Pract, 2018)
The collection of journal articles, systematic reviews, and reports published over the last decade that attest to the potential of digital technologies to achieve health workforce improvements across all aspects of the health system is vast. As a capacity-building mechanism, digital technology has potential for low- and middle-income countries (LMICs) to support development of the health workforce, including those health workers based in remote or rural areas, to train, motivate, support, monitor, and pay them. The purpose of this scoping review to present, at a high level, the state of the evidence and best practices in digital strategies for human resources for health and to propose a roadmap for a research agenda to fill identified gaps in the evidence. A variety of peer-reviewed and gray literature sources were searched using selected key terms related to digital health and health workforce, limited to materials published from 2010 to 2018. More than 70 articles, reports, and blog posts were reviewed, with in-depth analysis of 29 articles. Findings show that a range of digital health solutions for health workforce development have been tested and used, such as for health worker training, provider-to-provider communication and professional networking, and supervision of and performance feedback to health workers. There is some evidence of improved efficiency and effectiveness, at least at the level of pilots or small-scale projects. There is, however, a growing urgency in global health to move beyond small-scale demonstration projects and to define the capital and recurring costs of implementation and scale up of digital health interventions, including the return on investment. The next frontier is to select, adapt, and implement at scale those digital health interventions for health worker development and management found to be most promising.